PENGARUH PENAMBAHAN HIGH DENSITY POLY ETHYLENE (HDPE) DAN OLI BEKAS SEBAGAI BINDER PADA BATA RINGAN DENGAN VARIASI FILLER - Silviyati, Idha (KINETIKA, 2019)
Plastic is one of the polymer materials that is widely used in daily lives, one of them is High Density Poly Ethylene (HDPE) polymer which is the one type of the large contributors of plastic waste, and also believed to cause environmental and health problems. One of advanced material is lightweight brick which has become an innovation in building materials. Lightweight Hebel brick (celcon) is an infrastructure product that is widely used in this day. This study is entitled High Density Poly Ethylene (HDPE) Polymers as Binders in Lightweight Hebel Bricks (Celcon). Referring to the research master plan of the Sriwijaya State Polytechnic namely appropriate technological and industrial innovation and technology development of mining products. In this study utilizing High Density Poly Ethylene (HDPE) polymers as Binder and Portland Cement type I and silica Sand as Filler, in the process of making Lightweight Hebel Bricks (Celcon). The comparison of the Filler and Binder are 30:70, 40:60, 50:50, 60:40, 70:30 in %wt. Sample testing is done by testing the compressive strength, analyzing water absorption, density and SEM & EDX. The results showed that the compressive strength produced is included in quality I and quality III according to SNI 03-0349-1989 which in the variation of filler sample A has a compressive strength of 224.67 kg / cm2 and variation of filler sample B is 40, 45 kg / cm2 . The value of water absorption produced is also still below of the maximum limit, which is 25% which in the variation of sample A filler is 0.97% and the variation of filler sample B is 2.42%. The density values obtained are included in the medium density for filler variation of sample A, which is 900 kg / m3 and high density for variation of filler sample B, which is 1800 kg / m3 . By SEM-EDX analysis results showed that sample A has more porosity when compared to variations of sample B filler. In terms of economic analysis, the advantage of using plastic as material in making hebel bricks is the cost of making it economically due to the presence of plastic that is easily found.